Peningkatan Hasil Belajar Siswa Kelas IV SDN Nglambangan 01 Melalui Pendekatan Berdiferensiasi - Pramesti Wahyu Fandini; Hartini Hartini; Fitria Aris Dimyati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
In the classroom, learning outcomes are significantly impacted by the diversity of learners. Differentiated learning is a tactic that educators can employ to enhance students' learning outcomes. The purpose of this study was to enhance students' learning results in Indonesian language courses, particularly in transitive and intransitive sentence construction. Three components—visual, auditory, and kinesthetic—were used in this study's diversified learning approach. This study started with pre-cycle activities and used a two-cycle classroom action research approach. Planning, carrying out, observing, assessing, and reflecting were all done in each cycle. Based on the pre-cycle tasks, only four students (40%) completed them, while six students (60%) did not, with an average score of 65. The percentage of complete students increased to five (50%) in cycle I , whereas five (50%) of the students with an average score of 75 were not complete. There was a rise once more in cycle II, with an average score of 78, and 8 students (80%) who were complete and only 2 students (20%) who were not. The study's findings suggest that tailored instruction can enhance students' learning outcomes in Indonesian classes, particularly in class IV transitive and intransitive phrases. SDN Nglambangan 01.